Simulation of CO₂ capture process using different type of solvents: article - Mohamad Nazir, Mohamad Hidayatur Rahman; Mohd Salleh, Ruzitah; Shah Buddin, Meor Muhammad Hafiz (2018)
High amount of carbon dioxide is not suitable for the Earth as it can cause various environmental problems such as greenhouse gas effect as well as rise of Earth temperature. This phenomena can cause the elevation of sea water level due to melt of iceberg in North Pole and South Pole. However, the amount of carbon dioxide gas can be reduced by capturing the gas by using absorption process. This research project used Aspen HYSYS V8.8 in order to simulate the absorption process that consist absorber tower. distillation column, heat exchanger and pump. The feed of flue gas come from coal power plant which is about 5.35 % of carbon dioxide. Blending of piperazine (PZ) and monodiethanolamine (MDEA) was used in this study as the solvent in capturing carbon dioxide. The solvent can be regenerated by using stripper column that generate heat from the boiler thus strip the carbon dioxide from solvent. From this simulation, 0.1 MDEA and 0.1 PZ with 0.8 of water composition was chose as the best solvent which can fully absorbed carbon dioxide present which was 7820.9508 kg/h. Later on, the absorber tower was tested with solvent temperature in range 40° C - 100° C. Increasing feed solvent temperature will reduce the CO₂ absorption capacity.